Quantitative Analysis of Lanthanide Ions in LiCl-KCl Molten Salt by Normal Pulse Voltammetry - Kim, Tack-Jin; Kim, Gha-Young; Kim, Si-Hyung; Shim, Joon-Bo; Ahn, Do-Hee; Paek, Seungwoo; Jung, Yongju (Asian Journal of Chemistry, 2014)
An electrochemical approach to determine the lanthanide concentrations by normal pulse voltammetry was presented in the binary system of gadolinium (Gd) and lanthanum (La) as a part of the long-term goal to predict the total lanthanide concentrations in multi-component molten salt. The experimental conditions were optimized in terms of the pulse width and pulse period and a calibration curve was constructed in the molten salt with gadolinium ions. The limiting current of normal pulse voltammetry increased with gadolinium concentration with an excellent linearity in a concentration range of below 2 wt %. In addition, the total concentration of lanthanides in the binary solutions was estimated on the basis of the calibration curve. The maximum currents taken in the binary solutions of Gd and La were excellently fitted to the calibration curve, indicating that the total amount of lanthanides can be determined by normal pulse voltammetry technique.